Perception of Asaba People in Delta State Nigeria towards National Community Response to Covid-19 (American Journal of Medical Science and Innovation, 2024)
The 2019 coronavirus pandemic has caused global concern and led to measures such as hygiene, isolation, and social distancing. 99.5% of respondents knew about COVID-19, according to a Nigerian newspaper report, and most of them cited the internet, social media, and television as their main information sources The majority of defensive methods, according to 82.3% of respondents, include good cleanliness, self-isolation/social distance, face masks/gloves, and prayer. Also, 52.1% of respondents, however, said that the government was not doing enough to stop the pandemic in Nigeria. People who were well-informed on COVID-19 felt favorably about the country’s reaction. Most responders did not comply with preventive measures because they thought the pandemic was more of a hoax than a real threat. An accurate information dissemination plan is advised to guarantee adherence to preventive measures and to increase public awareness of the pandemic. In view of the ongoing epidemic, the study emphasizes the necessity of precise information dissemination tactics to guarantee adherence to preventive measures.